The self-made map : cartographic writing in early modern France - Conley, Tom (University of Minnesota Press, 1996)
In this wide-ranging and fascinating work, Tom Conley demonstrates that "a new cartographic impulse" during the French Renaissance gave rise to a new sense of self, one defined in part by the relationship of self and space